'Mormon reactions to The Book of Mormon'. Issue 2 (3rd July 2021) - Hale, Adrian
Abstract: The sustained success of the Broadway musical The Book of Mormon posed a major dilemma for the Mormon Church 1 and for many individual Mormons who revere the scripture from which the musical comedy takes its name. As a minority religion in the USA, the Mormon Church has endured over 190 years of persecution, public ridicule and marginalisation, much of which has been prompted by media and religious opposition to the Church's distinctive doctrines and scripture. Naturally, Mormon sensitivity to criticism – including humour which targets its core doctrines – remains high, given this historical legacy of wider community hostility. Nevertheless, the Mormon Church responded with what commentators saw as a unique and good-natured official public relations/proselyting campaign, capitalising on the musical's success. It signalled what can be referred to as a mature and creative policy/culture of tolerance, and this policy probably encouraged some members to attend the musical. This paper investigates the Church's official response to the musical, looks briefly at Mormon humour, and presents the results of a survey amongst Mormons who watched the show, to see if Mormons can laugh at The Book of Mormon.